PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IX SMP NEGERI 1 KAMPAR TIMUR - Yani, Casmi Fitri; Zuhri D, Zuhri D; Murni, Atma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research was the low ability of students mathematical understanding which effect to the lower score of mathematics learning outcomes in junior high school. The type of this research is experimental research and using the static group comparison design. The population in this research were all grade IX students of SMP Negeri 1 Kampar Timur. The sample in this research consists of two class, where the IX1 as an experimental class and the IX2 as a control class. The aim in this research was to know the effect of implementation discovery learning model toward students mathematical understanding ability based on KD 3.7 Create the generalization of the surface area and the volume of curved side geometry (tube, cone, and ball), and KD 4.7 Complete the contextual problems which are related to the surface area and the volume of curved side geometry (tube, cone, and ball), and also the combination of some of the curved side geometries. The instruments in this research were mathematical early ability test and the mathematical understanding ability test (postest). The result of mathematical early ability test was used for determining the sample of class. The postest result was analyzed by nonparametric statistic test of Mann Whitney and the magnitude of the effect was calculated using the Cohen’s formula. The result of the research showed that implementation discovery learning model gave the positive effect toward the mathematical understanding ability. The implementation discovery learning model had a magnitude of the effect for 76% toward the students mathematical understanding ability at grade IX of SMP Negeri 1 Kampar Timur and included in the medium category.Key Words: Discovery Learning, Mathematical Understanding Ability.